EVALUASI KELAYAKAN USAHA BUDIDAYA IKAN BANDENG (Chanos chanos) SECARA SEMI INTENSIF DI KECAMATAN ULUJAMI, KABUPATEN PEMALANG - Sri Rejeki; Tita Elfitasari; Rizky Handayani (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2019)
Milkfish is one of the most widely cultivated fish species in Indonesia. The development of milkfish cultivation technology in the community is inseparable from its comparative and strategic advantages because milkfish can be cultivated in brackish water, sea water and even freshwater and tolerant to environmental quality changes. Technology of cultivation and seeding has been done by the community. Milkfish is not susceptible to disease. The prospect of the development of milkfish breeding business in Ulujami District has good potential due to market demand. The purpose of this research is to know the technical aspect, financial aspect, and business feasibility of milkfish cultivation in Ulujami District. This research method is interview that is using questionnaire for data retrieval. The problems that arise in the breeding business of milkfish enlargement is how the efforts to obtain good and profitable results in fulfilling the market demand by spending as less as possible because it affects the profitability of the milkfish farmer income. Data analysis methods are obtained from Payback Period (PP), which is located in Limbangan Village 0.34, Mojo Village 0.98 and Pesantren Village 5.85. Net Present Value (NPV), the farmer's NPV value is positiv.  Benefit Cost Ratio (B / C Ratio) of each village are 2.35 and 4. Results and conclusions are obtained based on the technical aspects of site selection, maintenance, milkfish harvesting and financial aspects of business feasibility it this worth to be. Keywords: Business Feasibility Evaluation, Cultivator In Ulujami District